Identification of the murine coronavirus MP1 cleavage site recognized by papain-like proteinase 2 - Kanjanahaluethai A. (2014)
The replicase polyprotein of murine coronavirus is extensively processed by three proteinases, two papainlike proteinases (PLPs), termed PLP1 and PLP2, and a picornavirus 3C-like proteinase (3CLpro). Previously, we established a trans-cleavage assay and showed that PLP2 cleaves the replicase polyprotein between p210 and membrane protein 1 (MP1) (A. Kanjanahaluethai and S. C. Baker, J. Virol. 74:7911-79, 2000). Here, we report the results of our studies identifying and characterizing this cleavage site. To determine the approximate position of the cleavage site, we expressed constructs that extended various distances upstream from the previously defined C-terminal end of MP1. We found that the construct extending from the putative PLP2 cleavage site at glycine 2840-alanine 2841 was most similar in size to the processed MP1 replicase product generated in a trans-cleavage assay. To determine which amino acids are critical for PLP2 recognition and processing, we generated 14 constructs with amino acid substitutions upstream and downstream of the putative cleavage site and assessed the effects of the mutations in the PLP2 trans-cleavage assay. We found that substitutions at phenylalanine 2835, glycine 2839, or glycine 2840 resulted in a reduction in cleavage of MP1. Finally, to unequivocally identify this cleavage site, we isolated radiolabeled MP1 protein and determined the position of [35S] methionine residues released by Edman degradation reaction. We found that the aminoterminal residue of MP1 corresponds to alanine 2841. Therefore, murine coronavirus PLP2 cleaves the replicase polyprotein between glycine 2840, and alanine 2841, and the critical determinants for PLP2 recognition and processing occupy the P6, P2, and P1 positions of the cleavage site. This study is the first report of the identification and characterization of a cleavage site recognized by murine coronavirus PLP2 activity.